Analysis of Maternity Satisfaction Level to Antenatal Care Quality in Primary Health Care Markanding Muaro Jambi 2016 - Berliana, Novi; Amelia, Deasy (Universitas STRADA Indonesia, 2018)
Quality health services is one of the basic needs of each individual community acquired, health care quality will be felt by the patient if delivery is felt exceed patient expectations. This study aims to assess the level of satisfaction with quality of services pregnant women antenatal care in Primary Health Care Markanding Muaro Jambi. This research is descriptive quantitative method SERVQUAL (Services Quality). The study population was all pregnant women who are still active during their pregnancy were more than twice in Health Center Markanding Muaro Jambi with samples from pregnant women who come to the health center during the study (1 month) is taken by total sampling. Methods of data collection using questionnaires. Data were analyzed with Cartesian Diagram. Based on the research that has been done shows that the satisfaction of patients (pregnant women) to antenatal care services in Health Center Markanding, given the level of conformity between expectation and reality on the dimensions of reliability of 65,6%, the dimension of confidence (assurance) of 69,8%, dimensions of concern (empathy) amounted to 62,1% and the dimensions of direct evidence (tangible) amounted to 69,1%. Priority improved by Cartesian diagram is the ability of midwifes to be responsive resolve patient complaints, attention to complaints of patients and their families, care for patients regardless of social status. most respondents are not satisfied with the services at the health center for antenatal care Markanding Muaro Jambi